An investigation of the quality of presentation slide design and oral communication in higher education - Wijayanti, Sri Hapsari; Widyastuti, Theresia Dian; Ristyantoro, Rodemeus; Pramono, Herry (Univeritas Papua, 2025)
Oral presentation methods utilizing presentation slides are prevalent learning activities in higher education. The workplace also frequently employs presentations to report project outcomes, disseminate new regulations, or convey ideas. This research aims to (a) investigate the evaluation of presentation slide design and text by lecturers and peers; (b) determine the perceived importance of oral presentations and the use of presentation slides in the workplace. This study employs a mixed-methods approach, combining quantitative and qualitative descriptive methods. Data collection involved questionnaires distributed to 222 active students in the 2023-2024 even-semester. Additionally, data were gathered through interviews with two students and four private company leaders in Jakarta and Bekasi, West Java. The results indicate that peer evaluations of presentation design are higher than those of lecturers. Peers assigned lower scores to visual aspects, while lecturers focused on text size. This research does not fully align with communication theory, emphasizing the 7-line pattern with seven words per line on a single presentation slide. Oral presentations in the workplace are considered crucial for career advancement. However, practical shortcomings persist, including poorly structured presentation slides, presenters' insufficient attention to the audience, presentation content lacking supporting data and facts, and presenters resorting to verbatim reading.